Immediate Occlusal versus Non‐Occlusal Loading of Implants: A Randomized Clinical Pilot Study. (30th September 2013) - Vogl, Susanne; Stopper, Marlene; Hof, Markus; Wegscheider, Walther A.; Lorenzoni, Martin
Abstract Background Immediate occlusal and non‐occlusal loading protocols have been discussed and, despite varying success rates, are considered viable in selected cases. Preoperative implant planning and intraoperative transfer are essential to the success of implant‐supported reconstructions in partially or completely edentulous jaws. Purpose This study was performed to compare clinical outcomes of immediate occlusal versus non‐occlusal loading of posterior implants. Materials and Methods Of 19 patients with 52 screw‐type implants replacing mandibular molars or premolars, nine patients with 21 implants were randomized to a study group that received immediate restorations with occlusal loading, whereas 10 patients with 31 implants were randomized to a control group that received provisional restorations without occlusal loading. Occlusal loading was defined as full loading in maximum intercuspidation. Single‐tooth or splinted multiunit restorations were incorporated by screw retention or cementation. Marginal bone defects (MBD), implant survival, and implant success were evaluated 12 months after insertion. Results Both groups revealed similar MBD levels consistent with previous reports. No implants were lost (overall survival: 100%) or found to fail (overall success: 100%). No significant intergroup differences were noted for any of the evaluated parameters. Conclusions Immediate restorations in partially edentulous mandibles demonstrated successful clinical and radiographic 12‐month results. Larger long‐term prospective studies are needed to confirm the final evidence and predictability of immediate functional loading as a standard treatment concept for partially edentulous jaws.